Performance of ad hoc routing protocols in mobile WiMAX environment - Azad, Md. Saiful; Anwar, Farhat; Rahman, Md. Arafatur (Springer, 2009)
Worldwide Interoperability for Microwave Access (WiMAX) is a technology that bridges the gap between fixed and mobile access and offer the same subscriber experience for fixed and mobile user. Demand for such type of mobile broadband services and applications are growing rapidly as it provides freedom to the subscribers to be online wherever they are at a competitive price with other significant facilities such as increasing amounts of bandwidth, using a variety of mobile and nomadic devices etc. The earliest version of WiMAX is based on IEEE 802.16 and is optimized for fixed and nomadic access, which is further extended to support portability and mobility based on IEEE 802.16e, also known as Mobile WiMAX. However, frequent topology changes caused by node mobility make routing in Mobile WiMAX networks a challenging problem. In this study, we focus upon those routing protocols especially designed for wireless networks. Here, we compare the performance of four ad hoc routing protocols (AODV, DSR, OLSR and ZRP) for Mobile WiMAX environment under the assumption that each of the subscriber station has routing capabilities within its own network. From our simulation, we found that ZRP and AODV protocols outperform DSR and OLSR.